Condiciones de vida de los productores agrícolas y productores artesanales de ladrillos en el Cantón Chambo,Provincia deChimborazo, en el período 2023 - Balla Naranjo, Jessica Johana (2025)
The objective of this research is to analyze the living conditions of agricultural producers and brick producers in the Chambo Canton, Chimborazo province, during the year 2023. The sample consisted of 210 agricultural producers and 109 brick producers. The research was developed using a deductive methodology with a quantitative approach, and it was documentary, field-based, and non-experimental in nature. Socioeconomic dimensions, education, housing, and health were considered, using a survey developed by INEC to assess the living conditions of the producers. For statistical analysis, hypothesis testing was employed to verify statistically differences, using Chi-square tests for qualitative variables and Mann-Whitney U tests for quantitative variables, after assessing the normality of the data. The study found statistically differences in variables such as monthly income, frequency of weekly working hours, monthly expenses, educational level, condition of walls, roofs, and floors of the houses, number of medical check-ups per year, and the most common diseases affecting both groups. It was concluded that brick producers have better living conditions compared to agricultural producers. It is suggested that government policies should address these specified differences to improve the living conditions of the residents who contribute significantly to the local economic activity.